Bacteriology of Indian ()il Sardine (Sardinella longiceps Valenciennes) Stored in Chilled Sea Water - T.S., Shetty; T.M.R., Setty (Fishery Technology, 2025)
The changes in the bacteriology of Indian oil sardine (Sardinella longiceps valenciennes) and the medium surrounding the fish during storage in chilled sea water (2 i 1Â°C) were detennined by the identification of bacterial isolates upto their generic level. The flora of the freshly caught fish consisted mainly Micrococcus spp., Bacillus spp., Flavobacterium spp., Pseudomonas spp., Acinetobacter spp. and Vibrio spp., While that of the freshly collected sea water consisted mainly Micrococcus spp., Vibrio spp., Pseudomonas spp., Arthrobacter spp., Bacillus spp. and Aeromonas spp. The flora of the fish and the medium surrounding the fish after 10 days storage consisted mainly of Pseudomonas spp., Vibrio spp., Flavobacterium spp., Acinetobacter spp. and Aeromonas spp.